Critical education, speaking the truth, and acting back - W. Apple, Michael (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Professor Apple describes his past experiences in South Korea, in order to highlight theimportance and risks of being a critical educator. He also points out that if the theory andpractice of critical education are simply understood as a specialized academic area, widely usedfor purposes of conversion in order to gain mobility in the social field of the academic power(Bordieu, 1984), they lose their value and power. On the contrary, their power and potential aremagnified when they are intimately connected with the social movements and struggles thatgive life to them.